Oral Health 4 Life: Design and Methods of a Semi-pragmatic Randomized Trial to Promote Oral Health Care and Smoking Abstinence among Tobacco Quitline Callers - McClure, Jennifer B. (Contemp Clin Trials, 2017)
Smokers are at high risk for oral disease. As a result, they represent an important target group for population- level, public oral health promotion efforts. While dental health professionals often address smoking with their patients, no systematic efforts have been made to offer smokers an intervention to improve their use of oral health care. This paper details the rationale, design, and methods of a large, semi-pragmatic, randomized clinical trial designed to address this gap. Participants are recruited via the Oregon, Nebraska and Louisiana state-sponsored tobacco quitlines and randomized to receive standard quitline care versus standard care plus a multi- modal oral health promotion program (Oral Health 4 Life) integrated within the quitline services. All participants are followed for 6 months to assess the impact of the intervention on smoking abstinence and utilization of professional dental care. In addition, the study will assess the cost of the intervention and provide practical guidance to states on whether the intervention is financially feasible to implement, should the intervention be effective. This study protocol may be useful to others interested in promoting oral health among smokers, those interested in partnering with tobacco quitlines to extend standard services to address other high risk health behaviors among smokers, or those interested in semi-pragmatic trial design.